Ending technocracy with a neologism? Avivocracy as a conceptual tool. (November 2018) - Hudson, Marc
Highlights: Technocracy is the label given to support for fully 'rationalised' governance; it is one of the defining features of Western modernism. I outline the origins of the word technocracy and its relationship with epistemic injustice and 'practicality'. I explore several possible candidates as antonyms, and their different inadequacies. Finally, I propose a neologism - avivocracy -. It foregrounds irreducible uncertainty, ambiguity and uncontrollability in the 21st century.